DI-088 The switch from originator to biosimilar growth hormone: patients' experiences. (25th February 2017) - Vlijmen, B Van; Gool, L Van; Kerstens, M; Burger, D; Hermus, A; Smit, J; Repping-Wuts, H
Abstract : Background: After introduction of biosimilar growth hormone (BGH), the departments of pharmacy and endocrinology discussed this introduction in our hospital. Due to the large difference in costs between the originator and the BGH, it was decided to start all new patients on BGH and switch existing patients to BGH. Purpose: To investigate patients' experiences in the switch from originator to BGH via a survey. Material and methods: The questionnaire, used in this survey, was distributed to all 207 adult patients who were switched in the period after introduction of the biosimilar in our hospital. All participating patients had over 1 year of experience in the use of BGH. The following issues were addressed: difficulties in switching from originator to BGH; patient education before, during and after the switch; effect of BGH; adverse effects of BGH; and use of the new injection system for BGH. Results: The questionnaire was completed by 79 patients (38.1%). 72% of patients concluded that there was no problem in switching to the biosimilar. Remarks were made on safety of the injection system (n=13), adverse effects (n=13) and safety of the biosimilar in general (n=11). 93% of patients were satisfied with the introduction of BGH. 95% of patients indicated that individual training on the new injection system had been conducted and 98% were confident in using the system. Regarding the efficacy of BGH, 81% of patients indicated that there was no difference with the originator. Differences were described in loss of energy, fatigue and increased transpiration. 16% of patients indicated that adverse effects differed from their former product, with muscle stiffness (n=6), joint pain (n=4) and tingling (n=4). In comparison with the formerly used injection systems, 90% of users indicated that the new system was easy to use. Patients scored the transition to BGH in the Radboudumc with 7.8 (range 1–10). Conclusion: Patients were satisfied with the switch to BGH. There were few side effects and problems were solved in terms of care for the patient. Good preparation and good explanation for patients can help ease the introduction of biosimilars. No conflict of interest